Poly(amidoamine) dendrimers: covalent and supramolecular synthesis. (September 2019) - Lyu, Z.; Ding, L.; Huang, A.Y.-T.; Kao, C.-L.; Peng, L.
Abstract: Dendrimers, a class of synthetic macromolecules which are notable for their well-defined ramified structures and unique multivalent cooperativity, hold great promise for developing various functional materials. Among all the reported dendrimers, poly(amidoamine) (PAMAM) dendrimers are the most extensively studied by virtue of their readily availability via robust synthesis as well as their dendritic structure and peptide/protein mimic features. Since the seminal report by Tomalia et al., various strategies have been made available for PAMAM dendrimers, including divergent and/or convergent synthesis alongside click chemistry. Nevertheless, preparation of high-generation and defect-free PAMAM dendrimers on a large scale remains challenging. To overcome the limitations, an alternative strategy based on self-assembling approach has emerged for dendrimer synthesis, where small dendritic components form large non-covalent supramolecular structures that mimic high-generation covalent dendrimers. This approach is easy to implement in practice and requires much less synthetic effort. Here, we present a brief overview of the different approaches established for PAMAM dendrimer synthesis. We start with a general introduction to dendrimers and the common strategies for dendrimer synthesis, and then we illustrate the specific approaches for PAMAM dendrimer synthesis and highlight the related advantages and limitations using representative examples. Although various strategies have been established for PAMAM dendrimer synthesis, innovative concepts and approaches are still in high demand for reliably preparing defect-free and high-generation dendrimers in large quantity.